Improving rice growth through different concentration of Gibberellic Acid (GA) application / Muhammad Waie Khairuddin - Khairuddin, Muhammad Waie (Faculty of Plantation and Agrotechnology, 2019)
Paddy or rice is the second most important crop in the world after wheat. In Asia most of people uses the rice as a staple food, so the deficiency of the supply in rice could be affects the whole population. Improved rice production is needed to fulfill the demand of food. Early establishment of rice is very crucial for better nutrient uptake, better sunlight absorption, and vigorous growth and reduce weed competition. Application of GA on rice could potentially improve its early establishment. A study was conducted in green house at UiTM Jasin, Melaka. The experimental was conducted using Complete Randomized Design (CRD) with 4 treatment and 5 replication. Treatment 1 is control without any GA application, treatment 2 applied with 1g GA in 16 liter of water, treatment 3 applied with 2g GA in 16 liter of water, and treatment 4 applied with 3g GA in 16 liter of water. For growth parameter are plant height, number of tiller, leaf chlorophyll data were taken data on 25 days after sowing (DAS) and 45 DAS. Plant were harvested after 45 days before leaf area index and dry weight were taken. Data show there were significant difference of plant height, leaf area index, dry weight and numbers tiller. The result showed with application of GA, rice growth was improved. However, did not affect the chlorophyll content which is there were no significant difference of chlorophyll content of the rice plant. Plant height of treatment 4 is better growth than others because of the highest concentration of GA applied. Over concentration of GA influenced plant lodging and etiolation, so the optimum concentration needed to be applied for better growth.